2020
DOI: 10.24198/jkp.v8i3.1582
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Socio Demographic and Knowledge Factors Toward Therapy Options among Breast Cancer Patients

Abstract: The high prevalence and incidence of breast cancer patients poses a threat to the life quality of Indonesian women. Beside the patient’s condition, therapy options are also a factor faced by both the patients and their families. This research aims at describing socio demographic and knowledge factors relating to therapy options of breast cancer patients. Cross-sectional research was conducted directly to the people (community-based and hospital-based) from 198 cancer patients in the main region, West Java Prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Subsequently, from some literature, it was reported that spirituality is a strong predictor and promoter of psychological health [4]; [5]. It is in line with the results from [6], [7], [8]which states when the patient reaches the end of life, there becomes a need to fulfill spiritual needs. In addition to this, previous research had suggested that spirituality can increase the patient's endurance to mental health crisis after cancer diagnosis and treatment [9]; [10]; [11].…”
Section: Moresosupporting
confidence: 65%
“…Subsequently, from some literature, it was reported that spirituality is a strong predictor and promoter of psychological health [4]; [5]. It is in line with the results from [6], [7], [8]which states when the patient reaches the end of life, there becomes a need to fulfill spiritual needs. In addition to this, previous research had suggested that spirituality can increase the patient's endurance to mental health crisis after cancer diagnosis and treatment [9]; [10]; [11].…”
Section: Moresosupporting
confidence: 65%